2012
DOI: 10.1371/journal.pone.0046214
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Glutathione Peroxidase 3 through DNA Hypermethylation Is Associated with Lymph Node Metastasis in Gastric Carcinomas

Abstract: Gastric cancer remains the second leading cause of cancer-related death in the world. H. pylori infection, a major risk factor for gastric cancer, generates high levels of reactive oxygen species (ROS). Glutathione peroxidase 3 (GPX3), a plasma GPX member and a major scavenger of ROS, catalyzes the reduction of hydrogen peroxide and lipid peroxides by reduced glutathione. To study the expression and gene regulation of GPX3, we examined GPX3 gene expression in 9 gastric cancer cell lines, 108 primary gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 32 publications
5
49
0
Order By: Relevance
“…Our previous study revealed that GPx3 is downregulated in prostates of TRAMP mice and that disruption of GPx3 expression in TRAMP mice increased prostate cancer development and metastasis (50). It has been demonstrated that silencing GPx3 expression promoted cancer metastasis in human thyroid and gastric cancer cells (37,38). In the present study, it was notable that GPx3 expression level was upregulated following treatment with TGZ in human prostate cancer cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our previous study revealed that GPx3 is downregulated in prostates of TRAMP mice and that disruption of GPx3 expression in TRAMP mice increased prostate cancer development and metastasis (50). It has been demonstrated that silencing GPx3 expression promoted cancer metastasis in human thyroid and gastric cancer cells (37,38). In the present study, it was notable that GPx3 expression level was upregulated following treatment with TGZ in human prostate cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…It is well known that glutathione peroxidases are among the most important reactive oxygen species scavengers that protect cells from oxidative damage (36). Downregulation of GPx3 by hypermethylation has been revealed in numerous types of cancer (37)(38)(39)(40)(41)(42)(43)(44)(45), including prostate cancer (11,46,47). In prostate cancer, a negative correlation between GPx3 expression levels and poor clinical outcomes has been demonstrated (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that expression of these three genes may also represent potential markers for metastatic PPGLs. GPX3 silencing has been reported in metastatic tumors, such as in gastric carcinomas, where it increased migration and impaired mechanisms regulating reactive oxygen species (47). RERG was reported as a prognostic marker in breast cancer, whose expression correlated inversely proliferation, patient survival, and development of distant metastases (48).…”
Section: Discussionmentioning
confidence: 99%
“…GPx3 was found frequently down-regulated in cancer tissues including breast, lung and gastric cancer [47], which may due to its promoter hypermethylation [48][49][50]. Silencing or decreased activity of GPX3 is correlated with increased ROS level and contributes to cancer initiation [51] and metastasis [52,53].…”
Section: Discussionmentioning
confidence: 99%